Pattern bargaining as a means to coordinate wages in the nordic countries - Lars Calmfors (Research Institute of Industrial Economics (IFN), 2025)
The various form of pattern bargaining with manufacturing, as representative of the tradables sector, deciding the norm for wage increases in the Nordic countries are reviewed. This form of bargaining has been consistent with strong international competitiveness and has widespread support among practitioners based on informal analysis. It is, however, hard to build a convincing case in more formal modelling for the idea that wage leadership for the tradables sector is particularly conducive to wage restraint. The conclusion is rather that it is norm setting in itself, irrespective of by whom it is done, that promotes wage moderation. In the future, when changing demograhics may motivate a reallocation of labour to welfare services, a rigid application of international competitiveness norms may imply an undesirable status-quo bias. More weight should probably be given to overall labour market conditions and more relative-wage flexibility allowed.
Keywords: E24; J21; J51; 330; Pattern bargaining; coordination of wage setting; the Scandinavian model; Stackelberg leadership; social norms; labour reallocation